Analysis of interactive fixed effects dynamic linear panel regression with measurement error - Nayoung Lee; Hyungsik Roger Moon; Martin Weidner (Centre for Microdata Methods and Practice (cemmap), 2011)
This paper studies a simple dynamic panel linear regression model with interactive fixed effects in which the variable of interest is measured with error. To estimate the dynamic coefficient, we consider the least-squares minimum distance (LS-MD) estimation method.
Keywords: C23; C26; 330; dynamic panel; interactive fixed effects; measurement error; LS-MD estimation